Biomimetic nano-NOS mediated local NO release for inhibiting cancer-associated platelet activation and disrupting tumor vascular barriers. (October 2020) - Ma, Zhifang; Liu, Shi; Ke, Yue; Wang, Haozheng; Chen, Runhai; Xiang, Zehong; Xie, Zhigang; Shi, Qiang; Yin, Jinghua
Abstract: Platelets attribute to the hypercoagulation of blood and maintenance of the tumor vascular integrity, resulting in limited intratumoral perfusion of nanoparticle into solid tumors. To overcome these adversities, we herein present an antiplatelet strategy based on erythrocyte membrane-enveloped proteinic nanoparticles that biomimic nitric oxide synthase (NOS)with co-loading of l -Arginine (LA) and photosensitizer IR783 for local NO release and inhibition of the activation of tumor-associated platelets specifically, thereby enhancing vascular permeability and accumulation of the nanoparticles in tumors. A cRGD-immobolized membrane structure is constructed to actively target platelets and cancer cells respectively, through overexpressed integrin receptors such as integrin αIIb β3 and αv β3, accelerating the inhibition of platelet activation and endocytosis of nanoparticles by tumor cells. Bio-mimicking the arginine/NO pathway in vivo, synergistical delivery of LA and IR783 enables LA molecules readily oxidize to NO with O2 that is mediated by activated IR783, the resulted NO not only retards the activity of platelets to disrupt the vascular integrity of tumor but also enhances toxicity to cancer cells. In addition, NIR-controlled release localizes the NO spatiotemporally to tumor-associated platelets and prevents undesirable systemic bleeding substantially. The reduction of the hypercoagulable state is further demonstrated by the down-regulation of tissues factor (TF) expression in tumor cells. Our study describes a promising approach to combat cancer, which advances the biomimetic NOS system as the potent therapeutic forces toward clinic applications.